A (des)institucionalização da fé: um olhar sobre o processo de reconfiguração religiosa evangélica no Brasil - Paradela, George Jeovanholi (2021)
Modernity with its secularization process provoked a profound reconfiguration in religious dynamics. Some noticeable aspects of this reconfiguration are the subjectivation/individualization of beliefs and deinstitutionalization, that is, the loss of institutional power to legitimize belief systems. This research seeks to understand this process of religious reconfiguration in the Brazilian evangelical field from the movements of deinstitutionalization of this scenario. Having as a guiding point to understand how the "undetermined evangelicals" and "without religion" are an expression of this process of deinstitutionalization of faith, our research will identify these possible expressions of deinstitutionalizing faith and understand the criticism that underlies this path of faith that manifests itself in an unorthodox way.(AU)